Arduino based Colour Sensing System with Real-time RGB Display on LCD - Gourav Vivek Kulkarni; P. Brisli Jacob; Akshay P. Rao; Raksha Sai Rannorey; Nidhi B.C; Mayura S Yogi (International Journal of Advanced Robotics and Automation Technology, 2024)
Using a microcontroller Arduino UNO and TCS3200 color sensors, this project investigates the creation of a color measuring system. Colour sensors operate by emitting light onto an object and analyzing the reflected wavelengths to determine its colour. Our system is designed to detect a wide range of colours with high precision and display the corresponding Red-Green-Blue (RGB) values in real-time on a liquid crystal display (LCD). The TCS3200 sensor, developed by Texas Advanced Optoelectronic Solutions Inc., is central to this system. It includes an array of photodiodes and uses white LEDs to illuminate the target object. The sensor may measure the amount of red, green, and blue light reflected from an object by choosing the right photodiode array. The Arduino UNO processes it and then shows the RGB values it noticed on the LCD. In addition to the primary functionality of colour detection, the system is designed for future integration with a WIFI module to enable wireless communication and expand its applications. This project demonstrates the practical application of Arduino-based systems in tasks such as object sorting, quality control, and automation, highlighting the versatility and effectiveness of using affordable colour sensors in various industrial and consumer applications.
Keywords: Arduino uno; Colour Sensor; RGB Detection; TCS3200; liquid crystal display (LCD)